Regulatory Chill and the Effect of Investor State Dispute Settlements - Eckhard Janeba (Center for Economic Studies and ifo Institute (CESifo), 2016)
Legal conflicts between multinational firms and host governments are often decided by international arbitration panels - as opposed to courts in the host country - due to provisions in international investment agreements known as Investor State Dispute Settlements (ISDS). Critics fear that ISDS panels favor multinational firms, and thus make governments reluctant to adopt appropriate policies (regulatory chill). In this paper I develop an economic model to define regulatory chill and to analyze the effects of ISDS. Regulatory chill occurs when losses from regulatory mismatch are intermediate rather than very high. Moreover, if national courts are more likely to decide in favor of the host government than an international court, a unilateral shift to ISDS by one country is welfare worsening for the country. The net welfare change is more favorable, and sometimes - but not always - positive, when i) (symmetric) countries switch together to an ISDS based system, and when ii) foreign investment responds elastically to profit conditions.
Keywords: F23; F53; H25; 330; Investor State Dispute Settlement; TTIP; regulatory chill; international investment agreement; foreign direct investment